The research of indicators of speed of movements at girls in rowing - Богуш, Владимир; Гетманцев, Сергей; Богатырев, Константин; Смирнова, Ирина; Сокол, Ольга; Резниченко, Оксана (Slobozhanskyi Herald of Science and Sport, 2017)
V. Bohush, S. Hetmantsev, K. Bohatyryov, I. Smirnova, O. Sokol & O. Reznichenko Purpose: to investigate indicators of physical quality of speed and components of its elements. Material & Methods: girls of three age groups of different sports qualification, who specialize in rowing, were examined. Rate, time and speed of the single movement, frequency of movements were defined by the developed by us technique of measurement of effect of training action, and also sensomotor reactions to sound and light irritants when modeling conditions of training and competitive activity were investigated. Results: the conducted researches characterize specific psychophysiological features of organism of a sportsman. It is possible to apply the offered technique of the research of effect of training action to the purposeful studying and development of physical quality of speed in the training process. Formation and improvement of motor abilities in the concrete aged ranges is carried out in connection with high rates of development of morphological and functional indicators in the sensitive periods. Conclusions: the age of 13–18 years has the most optimum prerequisites for the improvement of motive qualities and formation of speed of movements. Changes of rate, time, speed, frequency of movements, time of sensomotor reactions to sound and light irritants occur under the influence of training.